Actividades artísticas y la práctica de valores - Anchatuña Pichucho, Josselyn Andrea (2016)
This research project was carried out a theoretical explanation of the concept on artistic activities in order to deep into the importance and use having them in early childhood Education. The values´ practice and development in children who are the direct beneficiaries of this project. On this premise, an Institution of Latacunga Canton was selected to develop the project. First, a diagnostic on the institutional situation was made where it was clearly evident that the Educational Community does not practice the values. A survey as an instrument technique was applied to collect real information from the institution. Also, a non-experimental quantitative theory was necessary for this study and the development of this researching project. Secondly, the results were analyzed, identifying where there are not trainings and a correct guidance on which it involves the practice of values inside of the institution. So that this is a decisive factor for the development of the personality of all members of the Educational Community especially with children, in this regard the proposal submitted previously had a completion factor, and it is necessary a socialization with all the members of Educative Community about what are the artistic activities, which implies the values practice for the personality development of it. As a result of this research project gathering bibliographic information that helped develop of this proposal and be able in the future to create a manual artistic activities for the proper practice of values.